SAT0613 High prevalence of subclinical atherosclerosis in gout and asymptomatic hyperuricemia: a study based on carotid ultrasound. (15th June 2017) - Bertolazzi, C; Gutierrez, M; Espinosa, R; Martínez-Lavin, M; Silveira, LH; Lozada, C; Moreno, J; Cruz, E; Olivares, B; Pineda, C; Lozada, AC
Abstract : Background: Accelerated atherosclerosis is known in gout. Hyperuricemia is considered an independent risk factor for cardiovascular (CV) disease. Evidence supporting both proatherogenic and prothrombotic states in HU is also published Ultrasound (US) measurement of the carotid intima-media thickness (cIMT) is a recognized measure of premature subclinical atherosclerosis with a predictive value respect to vascular events. Objectives: To determine the prevalence of increased cIMT, as sign of subclinical atherosclerosis, by an automated US method, and the associated risk factors in patients with gout and asymptomatic hyperuricemia (aHU) Methods: 138 patients with gout, 105 with aHU and 99 age and sex matched healthy controls were enrrolled. For all patients were recorded: clinical history, disease duration, smoking, ischemic heart disease, comorbidities (diabetes mellitus, high blood pressure, dyslipidemia, renal insufficiency, obesity), and current therapy. ESR and serum CRP, total and HDL cholesterol, triglycerides, glucose, creatinine and uric acid were recorded. Patients with history of CV and cerebrovascular events or autoimmune diseases were excluded. US examinations of both common carotids were performed by an experienced sonographer trained in cIMT examination, with a Esaote My Lab 70XVG, equipped with a linear probe (4–13 MHz) and an automatic IMT measure software. The definitions of Mannheim cIMT Consensus were adopted Results: A total of 684 common carotids were assessed. The prevalence of increased cIMT was 47.1%, 47.6% and 1% in patients with gout, aHU, and control group, respectively. The final adjusted logistic regression for patients with gout showed that time of disease progression (OR =0.79, 95% CI 0.66–0.95) and previous smoking (OR =0.32, 95% CI, 0.10–0.97) were associated with cIMT increase (p<0.05) whereas the uric acid levels (OR =1.66, 95% CI 1.07–2.56) was associated with an increased cIMT in aHU. No significant correlation was found with the other variables. No differences in US findings were found between gout and aHU (p=0.936). There was a significant difference in cIMT in gout versus control (p=0.0001) and aHU versus control (p=0.0001). Conclusions: Our results demonstrate that patients with gout and aHU without clinically evident cardiovascular disease have a high prevalence of subclinical atherosclerosis. Disease duration and levels of uric acid are independent factors related with increased cIMT in gout and aHU respectively. These results support the importance of screening for CV risk and to include carotid ultrasound in CV prevention strategies in these patients. Disclosure of Interest: None declared